Children with nighttime fears: Fears content, habits and sleep patterns and behavior problems - El Rafihi-Ferreira, Renatha (2021)
Nighttime fears in children can affect their sleep and daytime behaviors. This study aimed to verify in preschoolers with intense nocturnal fears: 1) the content of fears; 2) the effect of sex and age on the frequency and contents of fears; and 3) the habits and patterns of sleep and behavior problems of these children. The study included a sample of 71 parents of children aged 4 to 6 years old (51% girls) with intense nighttime fears, who answered questions about fears, sleep and behavior problems of their children. Fear of “ghosts”, “dark”, and “scary dreams” were the most#common fears, while “dark” and “sleeping away from parents” were the most intense. Few gender differences were found; however, age was a significant variable for 27.2% of the fears assessed – with older children presenting more fear than the younger. Inadequate sleep patterns and sleep routines were identified, such as late bedtime, delay to fall asleep, and frequent night waking and also internalizing behavior problems. These results suggest the need for treatment aimed at frequent nighttime fears, similar for boys and girls, and general guidelines on sleep hygiene provided to parents of preschoolers as a way to prevent inappropriate habits and patterns.